Incidence of Neck Pain in Patients With Concussion in a Pediatric Emergency Department. Issue 4 (22nd April 2022) - King, Jeffrey A.; Rodriquez, Brieana; Kim, Irene; Nimmer, Mark; Nelson, Lindsay D.; Szabo, Aniko; Dong, Huaying; Thomas, Danny
Abstract : Objectives: The aims of the study were (1) to determine the frequency of neck pain in patients diagnosed with mild traumatic brain injury (mTBI) or concussion in a pediatric level 1 trauma center emergency department (ED), (2) to identify variables associated with neck pain in this population, and (3) to report on aspects of care received in the ED including imaging and medication use. Methods: This is a retrospective chart review of 652 patients presenting to a pediatric ED with diagnosis of concussion/mTBI. Charts were reviewed for the following information: baseline demographic information, mechanism of injury, cause of mTBI, presence or absence of neck pain, point tenderness in the neck on physical examination, and whether the patient followed up within our health system in the 6 months after injury. Charts were also reviewed for other concussion-related symptoms, medication given in the ED, imaging performed in the ED, cervical spine clearance in the ED, and referrals made. For those patients who did have follow-up appointments within our system, additional chart review was performed to determine whether they sought follow-up treatment for symptoms related to concussion/neck pain and the duration of follow-up. Statistical analyses focused on the prevalence of neck pain in the sample. We subsequently explored the degree to which neck pain was associated with other collected variables. Results: Of 652 patients, 90 (13.8%) reported neck pain. Acceleration/deceleration injury and motor vehicle accident were predictive of neck pain. Neck pain was less common in those reporting nausea and vomiting. Direct impact of the head against an object was associated with reduced odds of neck pain, but after adjusting for other variables, this was no longer statistically significant. Patients with neck pain were older than those without neck pain. Patients with neck pain were more likely to receive ibuprofen or morphine and undergo imaging of the spine. They were also more likely to receive a referral and follow-up with neurosurgery. There was no significant difference between groups with respect to concussion-related follow-up visits or follow-up visits to a dedicated concussion clinic. Conclusions: Neck pain is a common symptom in pediatric patients with mTBI, although it was more likely in older patients and those presenting with acceleration/deceleration mechanisms. Although patients with neck pain were more likely to receive a referral and follow-up with neurosurgery, they were not more likely to have concussion-related follow-up visits. Indeed, most patients had no follow-up visits related to their concussion, which supports the notion that concussion is a self-limiting condition.